Dynamics of the production of Manihot esculenta Crantz in the municipality of Arapiraca, Alagoas (Research, Society and Development, 2020)
Cassava (Manihot esculenta Crantz) is one of the most important crops in tropical and subtropical regions of the world, occupying the fourth position among basic crops and responsible for being the food base of millions of people around the world. Brazil is one of the largest world producers of this culture and the Northeast region contributes significantly to national production. In Alagoas, the municipality of Arapiraca stands out as an important producer of cassava, so it is pertinent to know the local productive dynamics. In this sense, the objective was to analyze the performance of the cassava production variables during the 21-year period (1998-2018) in the municipality of Arapiraca, thus seeking to contribute to the understanding of the dynamics of this productive segment. The production data were obtained from the database of Municipal Agricultural Production - Temporary Crops of IBGE, using the Automatic Recovery System (SIDRA). To simultaneously analyze the studied variables, a Principal Component Analysis (PCA) was used. There were strong fluctuations in the variables analyzed, especially regarding the planted and harvested area. Cassava production in Arapiraca suffered a reduction in its participation in state production, as well as losses in productivity. Principal Component Analysis (PCA) explained 85.16% of the original data variance in the first two axes, with the formation of three clusters that brought together years with similar productive characteristics. Given the importance of this culture for the municipality of Arapiraca, it is necessary to develop actions that seek to rescue and strengthen local cassava production.